Rancang Bangun Alat Demonstrasi Smart Garden Berbasis Website Dan Aplikasi Android Sebagai Bagian Dari Produk Kidi Iot Untuk PT. Telkom Indonesia - Reza Raihan Nur, Muhammad; Nur Ramadan , Dadan; Octaviana Mandasari, Adelia (eProceedings of Applied Science, 2024)
-The fourth industrial revolution, characterized bythe emergence of the Internet of Things (IoT), has brought significant changes in various aspects ofin various aspects of life, includingeducation. Vocational High Schools (SMK), in particular,are facing challenges in adopting IoT technology toprepare the next generation for the digital era.This abstract discusses the importance of human resources(HR) and collaboration between schools, government, and the private sector to overcome the challenges ofto overcome the challenges in IoT adoption. Government,through Presidential Regulation No. 9/2016 onMerdeka Belajar Program, took an important initiative torevitalize SMKs by developing a curriculum thataligned with industry needs, improving teacherteachers, and providing adequate educational infrastructure.adequate educational infrastructure. PT Telkom Indonesia Tbk contributes throughAntares IoT Platform by introducing KiDi IoT(Digital Industrial Class of Internet of Things), which offers apackage of mentoring services, facilities, and infrastructure forIoT learning for vocational schools and universities. This initiativeprovides an opportunity for teachers and students togain valuable skills and knowledgeabout IoT, a Smart Garden Demonstration tool based ondemonstration tool as a bridge tointroduce teachers and students of vocational schools and universities toIoT technology. This demonstration tool offers practicalin creating smart solutions based on IoT,improve digital literacy, and developproblem-solving skills. This demonstration toolapplies IoT technology in monitoring air temperature,air humidity, water tank and soil moisture and thencontrol the pump. Keywords- Internet of Things, Smart Garden, Industrial RevolutionIndustrial Revolution, KiDi IoT, Education